Influence of TiO2 precursors on BaTiO3 by liquid phase precursor method. Issue 10 (December 2015) - Roh, Yoon-Ah; Humayoun, Usama Bin; Song, Young-Hyun; Kakihana, Masato; Masaki, Takaki; Yoon, Dae-Ho
Abstract: Barium titanate (BaTiO3 ) powder was prepared from the liquid phase precursor reaction of barium acetate with different types of Ti raw materials. Powders were synthesized using barium titanate, lactate A, lactate B, and TiCl3 fired at 600, 800, 900, and 1000 °C. The effects of the addition of titanium raw materials on the nanostructure and synthesis efficiency were investigated in this work to develop nano-sized particles at a low firing temperature. BaTiO3 nanopowders with different size distributions were synthesized using a liquid phase precursor with a titanium lactate complex as the Ti source at a low temperature. Also, the morphology and size of BaTiO3 nanopowders were controlled by adjusting the barium and titanium precursor concentration and the type of titanium raw materials. The X-ray diffraction of powders calcined at different temperatures and compositions was undertaken. The average size of the nanopowders was identified using a scanning electron microscope which varied from 25 nm to 50 nm.